In vitro acaricidal activity of traditionally used medicinal plant against southern cattle tick Rhipicephalus (Boophilus) microplus (Asian Journal of Pharmaceutics (AJP), 2025)
Rhipicephalus microplus ( Boophilus) is an economy damaging cattle pest, and conventionalacaricides face issues like resistance and environmental toxicity. Sustainable alternatives are urgently needed.Objectives: The aim of the study is to determine the efficacy of crude Cassia auriculata flower extract in increasingthe mortality and inhibiting the development of the tick at multiple life stages. Materials and Methods: Theacaricidal potential of C. auriculata flower extract is evaluated against the southern cattle tick, R. microplus, bytesting four concentrations (25, 50, 75, and 100 μg/μL) across all major tick life stages. Crude flower extract ofC. auriculata is prepared and applied at concentrations of 25, 50, 75, and 100 μg/μL to eggs, larvae, nymphs, andadult ticks. Mortality and developmental inhibition were measured at each stage. Results: A clear dose-dependentresponse is observed. The lowest dose (25 μg/μL) caused only modest mortality, while 50 and 75 μg/μL resultedin significantly greater tick mortality. The highest concentration (100 μg/μL) produced nearly total mortality inall life stages, including eggs, larvae, nymphs, and adults. Conclusion: C. auriculata flower extract demonstratessubstantial acaricidal efficacy, especially at 100 μg/μL, against all life stages of R. microplus. The findingssupport its potential in integrated pest management as an herbal, eco-friendly, and effective alternative to syntheticacaricides.